Pengaruh Waktu Penyimpanan Larutan Oral Nutraceutical Ekstrak Bunga Delima Merah (Punica Granatum L.) Terhadap Perubahan Hambatan Pertumbuhan Bacillus Subtilis (In Vitro) - Ruchmana, Anditya Syahbana Indra; , drg. Mahmud Kholifa, MDSc (2017)
Bacillus subtilis causes food poisoning, sore throat, bacteremia and also found in dental caries. Nutraceutical oral solution of natural substances with antibacterial effects is required to treat it. Red pomegranate flowers is known as antibacterial for the content of alkaloids, flavonoids, saponins, phenolic, proantosianin, and tannins. It is necessary to storage oral nutraceutical using brown glass bottles at room temperature so oral nutraceutical stability can be maintained. This study was aimed to determine the effect of nutraceutical oral solution red pomegranate flower extract shelf life to growth inhibition changes of Bacillus subtilis. This study was an experimental study with post test only control group design. The method used was by measuring the diameter of transparant zone. The results showed average of diameter inhibition zone with oral nutraceutical not been stored, stored 7 days, stored 14 days, stored 21 days, stored 28 days respectively 8,626 mm, 7,980 mm, 7,864 mm, 7,328 mm, 6,718 mm. After tested by one way ANOVA the result was p=0,006 (p<0,05). Post Hoc LSD test showed p<0,05 after 14 days of storage, it could be concluded that nutraceutical oral solution red pomegranate flower's extract had not significant effect on growth inhibition changes of Bacillus subtilis up to 14 days of shelf life.